2022
DOI: 10.3390/s22030715
|View full text |Cite
|
Sign up to set email alerts
|

Sound Localization and Speech Enhancement Algorithm Based on Dual-Microphone

Abstract: In order to simplify the complexity and reduce the cost of the microphone array, this paper proposes a dual-microphone based sound localization and speech enhancement algorithm. Based on the time delay estimation of the signal received by the dual microphones, this paper combines energy difference estimation and controllable beam response power to realize the 3D coordinate calculation of the acoustic source and dual-microphone sound localization. Based on the azimuth angle of the acoustic source and the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Tao et al [13] presented the enhanced sound source localization and speech enhancement algorithm which reduce microphone cost and also reduces the complexity. The dual-microphone sound algorithm effectively identifies the sound location, as well as the speech enhancement algorithm, is more resilient and adaptive than the previous method, according to experimental data.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Tao et al [13] presented the enhanced sound source localization and speech enhancement algorithm which reduce microphone cost and also reduces the complexity. The dual-microphone sound algorithm effectively identifies the sound location, as well as the speech enhancement algorithm, is more resilient and adaptive than the previous method, according to experimental data.…”
Section: Literature Surveymentioning
confidence: 99%
“…enhanced sound source localization and speech enhancement algorithm [13] reduce microphone cost and also reduces the complexity Based on the literature review, a variety of deep learning techniques for improving speech were suggested. However, speech enhancement systems face challenges from unstable voice signals, poor microphone performance, expensive computing, and the problem of echo cancellation in the presence of background noise.…”
Section: Do Not Eliminate Echomentioning
confidence: 99%
“…The results showed that the suggested ImNMF can significantly improve no ise speech while also increasing the robustness of the signal in electric car noise environment. Tao et al [13] presented the enhanced speech signal source localization and enhancement system which reduces microphone cost and reduces complexity. Dual-microphone sound algorithm effectively identifies the sound location, as well as the speech quality improvement, is more resilient and adaptive than the previous method, according to experimental data.…”
Section: Literature Surveymentioning
confidence: 99%
“…where C is the speed of sound in air. As a result, (Ɵ) can be used to estimate the direction as (13),…”
Section: The Direction Of Arrival (Doa)mentioning
confidence: 99%
“…Over the past decades, there has been a growing demand for speech enhancement using microphone arrays in speech processing applications such as automatic speech recognition, mobile communications, and hearing aids [ 1 , 2 , 3 , 4 ]. Multichannel speech enhancement aims to reduce the additive noise and improve the quality of the speech signals obtained by multiple microphones placed in a variety of acoustic environments [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In many multichannel speech enhancement systems, beamforming algorithms, such as the minimum-variance distortionless-response (MVDR) beamformer [ 11 ] and the general transfer function generalized sidelobe canceler (TF-GSC) [ 12 , 13 ], have been employed to extract a desired signal, exploiting spatial information on the location of the sound sources.…”
Section: Introductionmentioning
confidence: 99%